INFLUENCE OF CALCINATION TEMPERATURE OF TIO2 POWDER FROM CAUSTIC FUSION PROCESS WITH ILMENITE CONCENTRATE AS PHOTOANODE ON DYE-SENSITIZED SOLAR CELL (DSSC) PARAMETERS: COMPREHENSIVE REVIEW - Putra Andrianto, Surya
According to Richard E. Smalley, energy occupies the top position as a global issue in 2050 because it is believed to be the key to solving problems of water availability, the environment, and the human population. To address environmental issues generated from fossil energy, the United Nations has formulated environmentally friendly energy as one of the factors in the 2030 Sustainable Development Goals. Sun and wind as renewable energies are believed to be able to maximize energy supply, especially in developing countries. The generation of solar cells that have the potential to be developed is dye-sensitized solar cell (DSSC). DSSC is a photoelectrochemical cell with the principle of energy conversion that resembles plant photosynthesis. The main components of the DSSC consist of photoanode, dye, electrolyte, and counter-electrode. Photoanodes act as energy converters for photons to excite electrons. Metal oxides that can be used as photoanodes are TiO2, ZnO, SnO2, and Nb2O5. One of the main sources of TiO2 in nature is ilmenite (FeTiO3) ore. In this literature study based research, engineering the TiO2 characteristics of ilmenite ore through calcination (heat treatment) aims to optimize the energy conversion value of DSSC. Based on this literature study, the literature used is related to the synthesis process of ilmenite concentrate using the caustic fusion method to the use of TiO2 as a DSSC photoanode. The limitation of the problem, namely the minimum weight percent TiO2 for photoanode materials is 90% and the difference in calcination duration and thickness of the TiO2 semiconductor layer is negligible. The fixed variable was the weight percent of TiO2 powder with the variable being the calcination temperature of TiO2 powder before it was applied to DSSC photoanodes. The results of research based on literature studies show that TiO2 powder synthesized ilmenite concentrate using the caustic fusion method has characteristics in the form of fine particle size, mesopore pore criteria, and the crystal structure is dominated by the anatase phase with a band gap energy of 2.6-3.0 eV. To obtain TiO2 nanoparticles, the sol-gel method can be done by adjusting the ratio of TiOSO4 and aquadest in the hydrolysis stage to accelerate the reaction and using NH4OH as a pH regulator. In addition, the addition of pluronic P123 also plays a role in pore formation. The increase in calcination temperature of synthesized TiO2 powder is directly proportional to the transformation of the anatase phase to rutile phase, crystallinity, and particle size but inversely proportional to the specific surface area, porosity, and band gap energy value. The highest DSSC efficiency occurs in the calcination temperature range of 450-550°C which correlates with the optimal characteristics of TiO2 as a photoanode.